Prevalence of cystic echinococcosis in pigs and goats slaughtered at a municipal abattoir in northern Peru - Zuñe Flores, David Joel; Livia Córdova, Giovana Nancy (REBIOL, 2026)
Cystic echinococcosis remains a neglected parasitic disease of public health concern in many developing countries, particularly in areas where livestock production and inadequate sanitary conditions coexist. This study aimed to estimate the prevalence of cystic echinococcosis and to evaluate potential risk factors in pigs and goats slaughtered at the municipal abattoir of Paita, northern Peru. A post-mortem inspection was conducted through systematic palpation and detailed macroscopic examination of lungs, heart, liver, spleen, and kidneys to detect hydatid cysts. Inspections were carried out weekly from January to June 2022. Data were processed using Microsoft Excel and statistically analyzed with SPSS version 22. The results revealed a prevalence of cystic echinococcosis of 1.6% in pigs, while no cases were detected in goats. Female pigs showed a higher prevalence (1.0%) compared to males (0.6%). The chi-square test applied to the evaluated risk factors showed no statistically significant association with the presence of hydatid cysts. Although the prevalence observed was low, the detection of cystic echinococcosis in slaughtered pigs highlights the need for continuous abattoir surveillance and strengthened control strategies to reduce the potential risk of transmission and its impact on public health. DOI: http://dx.doi.org/10.17268/rebiol.2025.45.01.04